Between Aesthetics and Politics: Socially Engaged Art on the Internet - Winiecka, Elżbieta (Poznańskie Studia Slawistyczne, 2019)
The author discusses the changes in the model of democracy that have occurred since the Internet began. The hierarchical model of representative democracy is replaced on the Web by participatory democracy. On the example of Siksa and Bread Resolution (Rozdzielczość Chleba), the author shows up the transformations of the model of literary communication on the Internet. She also indicates ethic role engaged art takes in the contemporary society. Artists that produce socially engaged art do it in the name of those who do not exist in public space, those whose voice is not heard and who cannot defend themselves. Nevertheless, the author comes to the conclusion that the real democratic revolution can only take place outside the Web.